2020
DOI: 10.1186/s12974-020-01904-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive impacts of arbovirus infections

Abstract: Arthropod-borne viruses or arbovirus, are most commonly associated with acute infections, resulting on various symptoms ranging from mild fever to more severe disorders such as hemorrhagic fever. Moreover, some arboviral infections can be associated with important neuroinflammation that can trigger neurological disorders including encephalitis, paralysis, ophthalmological impairments, or developmental defects, which in some cases, can lead to long-term defects of the central nervous system (CNS). This is well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 196 publications
(243 reference statements)
0
31
0
Order By: Relevance
“…Arthritogenic and neurotropic alphaviruses continue to spread around the world, leading to an increase in infections and, consequently, in the occurrence of associated arthralgia and neurological disorders [13,40]. Some arboviruses are now well described for their ability to access the CNS and cause short-and long-term neuropathology, potentially due to acute or chronic inflammatory states [40]. Neurological complications have been described in CHIKV-infected patients, in particular in children and the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Arthritogenic and neurotropic alphaviruses continue to spread around the world, leading to an increase in infections and, consequently, in the occurrence of associated arthralgia and neurological disorders [13,40]. Some arboviruses are now well described for their ability to access the CNS and cause short-and long-term neuropathology, potentially due to acute or chronic inflammatory states [40]. Neurological complications have been described in CHIKV-infected patients, in particular in children and the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the vast majority of viral infections present at least one neurological symptom during the acute phase, which can lead to neurological, behavioral, and cognitive sequelae months after the initial infection [ 2 , 6 ]. A recent report demonstrated that children (0.5–8 years) with severe viral CNS infections show enhanced risk of psychotic illness when they reach young adulthood [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral organoids were also chosen because they develop immunocompetent astrocytes that are key players in neuroinvasive disease response [13]. While mid-brain organoids are standard for PD research, they omit the cerebral cortex that is integral to viral pathogenesis in the human CNS [14]. Thus, the goal of this study was to define differences in cerebral organoids derived from an individual with PD versus an individual without PD so that these model systems may be used to inform future studies of viral CNS infections.…”
Section: Introductionmentioning
confidence: 99%